The urokinase receptor: Focused cell surface proteolysis, cell adhesion and signaling - Blasi, Francesco; Sidenius, Nicolai (FEBS letters, 2010)
Plasma membrane urokinase-type plasminogen activator (uPA)-receptor (uPAR) is a GPI-anchored protein that binds with high-affinity and activates the serine protease uPA, thus regulating proteolytic activity at the cell surface. In addition, uPAR is a signaling receptor that often does not require its protease ligand or its proteolytic function. uPAR is highly expressed during tissue reorganization, inflammation, and in virtually all human cancers. Since its discovery, in vitro and in vivo models, as well as retrospective clinical studies have shown that over-expression of components of the uPA/uPAR-system correlates with increased proliferation, migration, and invasion affecting the malignant phenotype of cancer. uPAR regulates the cells–extracellular matrix interactions promoting its degradation and turnover through the plasminogen activation cascade.